2021
DOI: 10.1186/s12974-021-02210-2
|View full text |Cite
|
Sign up to set email alerts
|

Expression of SARS-CoV-2-related receptors in cells of the neurovascular unit: implications for HIV-1 infection

Abstract: Background Neurological complications are common in patients affected by COVID-19 due to the ability of SARS-CoV-2 to infect brains. While the mechanisms of this process are not fully understood, it has been proposed that SARS-CoV-2 can infect the cells of the neurovascular unit (NVU), which form the blood-brain barrier (BBB). The aim of the current study was to analyze the expression pattern of the main SARS-CoV-2 receptors in naïve and HIV-1-infected cells of the NVU in order to elucidate a p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 112 publications
(122 reference statements)
6
44
0
7
Order By: Relevance
“…It has been proposed that the neuroinvasion of SARS-CoV-2 through the BBB may occur via interaction of the viral spike protein with ACE2 expressed in the capillary endothelium, subsequently infecting CNS cells, including glia (Jha et al, 2021). Consistent with this, the receptors involved in SARS-CoV-2 infection including ACE2 were seen to be expressed in the cells of the neurovascular unit, especially in astrocytes and microglial cells (Torices et al, 2021). Recent studies also showed that human pericyte-like cells from brain organoids and endothelial cells from mouse cerebral microvessels can be infected by SARS-CoV-2 (Wang et al, 2021;Wenzel et al, 2021).…”
Section: Introductionmentioning
confidence: 80%
“…It has been proposed that the neuroinvasion of SARS-CoV-2 through the BBB may occur via interaction of the viral spike protein with ACE2 expressed in the capillary endothelium, subsequently infecting CNS cells, including glia (Jha et al, 2021). Consistent with this, the receptors involved in SARS-CoV-2 infection including ACE2 were seen to be expressed in the cells of the neurovascular unit, especially in astrocytes and microglial cells (Torices et al, 2021). Recent studies also showed that human pericyte-like cells from brain organoids and endothelial cells from mouse cerebral microvessels can be infected by SARS-CoV-2 (Wang et al, 2021;Wenzel et al, 2021).…”
Section: Introductionmentioning
confidence: 80%
“…In addition to ACE2 and TMPRSS2 , several other molecules have also been suggested to participate in SARS-CoV-2 cell entry, such as DPP4 , ANPEP , AXL , and ENPEP ( 30 41 ). ACE2 is detected in the CNS, namely, substantia nigra and brain ventricles, piriform cortex, neurons and some nonneuronal cells (astrocytes and oligodendrocytes from the middle temporal gyrus and posterior cingulate cortex) ( 52 54 ). TMPRSS2 is observed in oligodendrocyte precursor cells, astrocytes and microglial cells of the neurovascular units ( 53 , 54 ).…”
Section: Resultsmentioning
confidence: 99%
“…ACE2 is detected in the CNS, namely, substantia nigra and brain ventricles, piriform cortex, neurons and some nonneuronal cells (astrocytes and oligodendrocytes from the middle temporal gyrus and posterior cingulate cortex) ( 52 54 ). TMPRSS2 is observed in oligodendrocyte precursor cells, astrocytes and microglial cells of the neurovascular units ( 53 , 54 ). DPP4 and ANPEP are distributed in astrocytes and microglial cells of neurovascular units ( Table 1 ) ( 54 ).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have identified that co-infection with SARS-CoV-2 and influenza A led to increased pathological outcomes in animal models and human patients ( Alosaimi et al, 2021 ; Yang et al, 2021 ; Zhao et al, 2021 ). Increased expression of receptors for SARS-CoV-2, ACE2 and TMPRSS2, in human neuronal cells and microglia is reported in HIV infection ( Torices et al, 2021 ). Our study demonstrated a trend of enhanced expression of ACE2 in the gut epithelial lining in the villi during SIV infection in vivo , resulting in availability of abundant binding sites for SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%